Blue light exposure decreases systolic blood pressure, arterial stiffness, and improves endothelial function in humans. (29th August 2020) - Stern, Manuel; Broja, Melanie; Sansone, Roberto; Gröne, Michael; Skene, Simon S; Liebmann, Joerg; Suschek, Christoph V; Born, Matthias; Kelm, Malte; Heiss, Christian
Abstract: Aims: Previous studies have shown that ultraviolet light can lead to the release of nitric oxide from the skin and decrease blood pressure. In contrast to visible light the local application of ultraviolet light bears a cancerogenic risk. Here, we investigated whether whole body exposure to visible blue light can also decrease blood pressure and increase endothelial function in healthy subjects. Methods: In a randomised crossover study, 14 healthy male subjects were exposed on 2 days to monochromatic blue light or blue light with a filter foil (control light) over 30 minutes. We measured blood pressure (primary endpoint), heart rate, forearm vascular resistance, forearm blood flow, endothelial function (flow-mediated dilation), pulse wave velocity and plasma nitric oxide species, nitrite and nitroso compounds (secondary endpoints) during and up to 2 hours after exposure. Results: Blue light exposure significantly decreased systolic blood pressure and increased heart rate as compared to control. In parallel, blue light significantly increased forearm blood flow, flow-mediated dilation, circulating nitric oxide species and nitroso compounds while it decreased forearm vascular resistance and pulse wave velocity. Conclusion: Whole body irradiation with visible blue light at real world doses improves blood pressure, endothelial function and arterial stiffness by nitric oxide released from photolabile intracutanous nitric oxide metabolites into circulating blood.